Психодіагностичний потенціал опитувальника загального стану здоров’я та його україномовна адаптація - Барко, В. І.; Barko, V. I.; Євдокімова, О. О.; Yevdokimova, O. O.; Смірнова, О. М.; Smirnova, O. M.; Барко, В. В.; Barko, V. V.; Olena Yevdokimova (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 2 (109). - С. 406-421, 2025)
У статті здійснено комплексний аналіз психодіагностичних можливостей зарубіжного опитувальника загального стану здоров’я GHQ-28, розробленого в 1979 році Д. Голдбергом і В. Хіллієром. У структурі опитувальника на основі факторного аналізу визначено чотири субшкали – соматичні симптоми, тривожність / безсоння, соціальна дисфункція і важка депресія, кожна з яких містить сім пунктів. Показано, що опитувальник широко застосовується за кордоном для оцінювання здатності людини виконувати нормальні функції та діагностики певних відхилень дистресового характеру у стані психічного здоров’я. Наголошено, що актуальним завданням є україномовна адаптація GHQ-28. Проведено емпіричне дослідження за участю поліцейських і курсантів закладів вищої освіти Міністерства внутрішніх справ України зі специфічними умовами навчання, у межах якого розроблено україномовну версію опитувальника, а також встановлено його психометричні показники та середньостатистичні норми. Показано, що україномовний варіант опитувальника характеризується задовільними показниками внутрішньої узгодженості шкал, надійності (ретестової і паралельних форм), а також критеріальної валідності.

The article provides a comprehensive analysis of the psychodiagnostic capabilities of the foreign questionnaire on general health GHQ-28, developed in 1979 by D. Goldberg and W. Hillier. The structure of the questionnaire, based on factor analysis, includes four subscales, each of which contains seven items: somatic symptoms; anxiety; social dysfunction and severe depression. It is shown that the questionnaire is widely used abroad to determine a person’s ability to perform normal functions and diagnose certain distress-related deviations in the state of mental health. An empirical study was conducted with the participation of police officers and cadets of higher educational institutions of the Ministry of Internal Affairs of Ukraine with specific training conditions, in the course of which the Ukrainian version of the questionnaire was developed, and its psychometric indicators and average statistical norms were established. The study resulted in reliable, internally consistent scales with a high level of reproducibility. Thus, for all four scales of the questionnaire, the Cronbach’s α coefficient is greater than 0.70. The correlation coefficients between the results of the first survey and the scores obtained during the retest range from 0.87 to 0.90 (p < 0.01). The correlation between the Ukrainian version of the questionnaire and the original is also high, with correlation coefficients between the scales of the same name ranging from 0.82 to 0.91 (p < 0.05 and p < 0.01). The results of the factor analysis showed that the factor structure of the Ukrainian version fully reproduces the structure of the original, all items of the adapted questionnaire were included in the relevant factors. The study of criterion validity shows that the general health questionnaire has satisfactory indicators of the latter (based on the comparison of results with other questionnaires with known validity), the indicators of criterion validity range from 0.42 to 0.67. The questionnaire was also standardised, with average norms and standard deviations for individual scales and the overall health status indicator. The results scored by respondents on scale D (severe depression) of the questionnaire were minimal (100 % of the surveyed demonstrated a high level of health according to this indicator). Therefore, it was not possible to calculate correlations of this scale with the scales of other questionnaires. Scale D is very different from the other scales of this questionnaire in terms of the structure of the stimulus material due to the clinical nature of its statements. Consequently, the Ukrainian version of the questionnaire is characterised by satisfactory indicators of internal consistency of scales, reliability (retest and parallel forms), and criterion validity.
The Psychodiagnostic Potential of the General Health Questionnaire and its Ukrainian-Language Adaptation
Keywords: опитувальник загального стану здоров’я; психологічна діагностика; психометричні показники; стандартизація; статистичні норми; надійність; валідність; general health questionnaire; psychological diagnostics; psychometric indicators; standardisation; statistical norms; reliability; validity